EVALUASI IMPLEMENTASI KEBIJAKAN TENTANG TATANAN KEBANDARUDARAAN NASIONAL (STUDI PADA BANDAR UDARA SULTAN SYARIF KASIM II) - Ilman Nasution; Sujianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Based on direct observations in the field indicate that the airport system at Sultan Syarif Kasim II Airport is still not in accordance with the established policy. Preparation of the national airport system is based on aspects of spatial planning, economic growth, environmental sustainability, security and aviation safety. The indications can be formulated problems in this research that is how the policy of Airport order at Sultan Syarif Kasim II Airport and the factors that affect the Airport order policy at Sultan Syarif Kasim II Airport. The author uses William N. Dunn's theory of evaluating policies based on indicators of effectiveness, efficiency, adequacy, leveling, responsiveness and accuracy for analyze in this problem. This research was conducted in Pekanbaru City, using qualitative method. All answers obtained from informants / respondents and document that can be through observation, analyzed to get conclusions and suggestions. The results of this research indicate the implementation of the Airport system at Sultan Syarif Kasim II Airport is not in accordance with the established policy. While the factors affecting the Airport Regulation Policy at Sultan Syarif Kasim II Airport, the Spatial Planning Plan (RTRW) of Pekanbaru City can not be used as the foundation of development, quality and strength of Human Resources (HR) that has not been fulfilled, the limited authority of local government . Prolonged community land acquisition, limited public knowledge of this policy and fraudulent execution of duties between supervisor and supervisor. Keywords: effectiveness, efficiency, adequacy, leveling, responsiveness and accuracy